SYNTHESIS AND STRUCTURAL STUDIES OF 1-[(8-NITRONAPHTHO[2,1-B]FURAN-2-YL) CARBONYL] PIPERIDINE - E. Shruthi; V. P. Vaidya; C. R. Girija; S. Shalini (European Scientific Journal, ESJ, 2013)
Naphtho [2,1-b] furan-2-carboxyazide has been synthesized from ethyl 8-nitronaphtho [2,1-b] furan-2-carboxylate, by first converting into 8-nitronaphtho [2,1-b] furan-2-carboxyhydrazide , followed by diazotization. The reaction of carboxyazide with piperidine resulted in nucleophilic substitution reaction giving 1- [(8-nitronaphtho [2, 1-b] furan-2-yl) carbonyl] piperidine (NNFCP). The compound has been characterized by FT-IR, 1HNMR, Mass spectral data and X-ray diffraction analysis.